Vegetação de Mombeja - Vasconcelos, Maria Teresa (2013)
The habitats of the natural vegetation concerning the region between the localities Peroguarda, Beringel and Mombeja are presented. Based on the reasonable conservation and floristic diversity of the natural vegetation on the center of the extense cereal country on the South Alentejo province, the atrihution of a conservation status is proposed. Besides the well represented species which are described, the value of the site is enhanced by the presence of the rare species Adonis amua L. ssp. annua, Cynara tournefortii Boiss. & Reuter, Echium boissieri Steudel and Linaria hirta (L.) Moench. The phytosociological assotiations and its syntaxomie are presented and the habitas cited on Directive 92/43/EEC are referred: 92A0 - ash mediterranean ripanan galleries; 3280 constantly flowing meditermean rivers; 5330 - all types of thermo-mediterranean and pre-step pe brush; 6220 - pseudo-steppe with grasses and annnuals; 63 10 - sclerophillus grazed forest with the holmoaks